Nonopsonic phagocytosis of Pseudomonas aeruginoas: insights from an infant with leukocyte adhesion deficiency. - Pollard, A; Heale, J; Tsang, A; Massing, B; Speert, D (2001)
Children with leukocyte adhesion deficiency type I are at risk for overwhelming infection because their neutrophils lack surface beta 2 integrins (CD18/CD11) that normally interact with endothelial cell adhesion molecules and mediate migration to sites of bacterial invasion. In vitro studies of phagocytic cells from an infant with leukocyte adhesion deficiency type I demonstrated that complement receptor 3 (CD18/CD11b) mediates nonopsonic phagocytosis of some Pseudomonas aeruginosa strains and might play a control role in the control of Pseudomonas infections at sites where there are low levels of opsonins.